The impact of a maternal and offspring obesogenic diet on daughter’s oocyte mitochondrial ultrastructure and bioenergetic responses. Insights from an outbred mouse model - Xhonneux, Inne; Marei, Waleed F. A.; Meulders, Ben; Andries, Silke; Leroy, Jo L. M. R. (Frontiers in Physiology, 2023)
Obesity affects oocyte mitochondrial functions and reduces oocyte quality and fertility. Obesity may also increase the risk of metabolic disorders in the offspring. Children are likely to follow their parents lifestyle and diet, which also contributes to the increased prevelance of obesity across generations. We hypothesise that the impact of obesogenic (OB) diet and obesity on oocyte mitochondrial functions is different in offspring born to obese mothers compared to those born to healthy mothers. To test this hypothesis, we fed a control (C, 10% fat, 7% sugar) or an OB diet (60% fat, 20% sugar) to female mice (for 7 weeks (w)) and then to their female offspring (for 7w after weaning) in a 2x2 factorial design (C»C, n=35, C»OB, n=35, OB»C n=49 and OB»OB, n=50). Unlike many other studies, we used an outbred Swiss mouse model to increase the human pathophysiological relevance. Offspring were sacrificed at 10w and their oocytes were collected. Offspring OB diet increased oocyte lipid droplet content, mitochondrial activity and reactive oxygen species (ROS) levels, altered mitochondrial ultrastructure and reduced oocyte pyruvate consumption. Mitochondrial DNA copy numbers and lactate production remained unaffected.Mitochondrial ultrastructure was the only factor where a significant interaction between maternal and offspring diet effect was detected. The maternal OB background resulted in a small but significant increase in offspring's oocyte mitochondrial ultrastructural abnormalities without altering mitochondrial inner membrane potential, active mitochondrial distribution, mitochondrial DNA copy numbers, or ROS production. This was associated with reduced mitochondrial complex III and V expression and reduced pyruvate consumption which may be compensatory mechanisms to control mitochondrial inner membrane potential and ROS levels. Therefore, in this Swiss outbred model, while offspring OB diet had the largest functional impact on oocyte mitochondrial features, the mitochondrial changes due to the maternal background appear to be adaptive and compensatory rather than dysfunctional.